2017
DOI: 10.1590/1982-021620171917916
|View full text |Cite
|
Sign up to set email alerts
|

Tecnologias da Informação e da Comunicação (TIC) aplicadas à dislexia: revisão de literatura

Abstract: The current paper aims to present an integrative literature review of scientific articles published in national and international journals, approaching the use of information and communication technology (ICT) such as computers, tablets, iPad's, mobile phones, e-readers, virtual reality and virtual learning environments, applied to dyslexia. The database consists of scientific articles published between 2010 and 2015, from the following platforms: Science Direct/Elsevier, SciELO -Scientific Electronic Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
(58 reference statements)
0
3
0
10
Order By: Relevance
“…By complementing therapeutic interventions and traditional teaching, they address the aforementioned disadvantages of TI and offer new opportunities to engage the learner (se also Table 1). Based on literature reviews, we conclude that CBI and ICT can have positive effects on dyslexic children's learning development [41] and that they facilitate literacy acquisition for dyslexic children by minimizing difficulties in learning to read and write [42].…”
Section: Omputer -Based Interventionsmentioning
confidence: 96%
See 1 more Smart Citation
“…By complementing therapeutic interventions and traditional teaching, they address the aforementioned disadvantages of TI and offer new opportunities to engage the learner (se also Table 1). Based on literature reviews, we conclude that CBI and ICT can have positive effects on dyslexic children's learning development [41] and that they facilitate literacy acquisition for dyslexic children by minimizing difficulties in learning to read and write [42].…”
Section: Omputer -Based Interventionsmentioning
confidence: 96%
“…Third, research has shown that children may concentrate better while engaged in CBI than in traditional school tasks [47] Fourth, nowadays, ICT can provide interactive experiences which can motivate children at an early age and attenuate the impact of their own difficulties in the daily acquisition of reading and spelling skills [42].…”
Section: Programmentioning
confidence: 99%
“…De acordo com pesquisas recentes, o uso de TICs auxilia e reforça o processo de aprendizado de indivíduos disléxicos [Cidrim e Madeiro, 2017]. Em geral, os resultados sugerem que os recursos tecnológicos propiciam aos indivíduos com dislexia maior envolvimento nas atividades de leitura e compreensão de textos [Benmarrakchi et al, 2016;Skiada et al, 2014].…”
Section: Tics Aplicadas à Dislexiaunclassified
“…Como exemplo de aplicações, podem-se citar o uso na Educação Básica para o desenvolvimento de habilidades sociais (com o uso de mundos virtuais) e noções espaciais (Hew & Cheung, 2010;Lee & Wong, 2014;Merchant, Goetz, Cifuentes, Keeney-Kennicutt, e Davis, 2014); no Ensino Superior, para o desenvolvimento de habilidades cirúrgicas em cursos de medicina (Anjos, Nunes & Tori, 2012;Psotka, 1995), em cursos de Odontologia (Roy, Bakr & George, 2017;Tori et al, 2016) e no ensino de metodologia para engenheiros (Häfner, Häfner & Ovtcharova, 2013); e na Educação para Necessidades Especiais, para avaliar como determinados estímulos afetam o desempenho cognitivo como também registrar e armazenar dados de desempenho motor e cognitivo dos alunos (Cidrim & Madeiro, 2017;Ortiz-Catalan et al, 2014;Rosa et al, 2016).…”
Section: Realidade Virtual Na Educaçãounclassified